2019
DOI: 10.3390/en12112076
|View full text |Cite
|
Sign up to set email alerts
|

Minimum Energy Management Strategy of Equivalent Fuel Consumption of Hybrid Electric Vehicle Based on Improved Global Optimization Equivalent Factor

Abstract: A parallel hybrid electric vehicle (PHEV) is used to investigate the fuel economy effect of the equivalent fuel consumption minimization strategy (ECMS) with the equivalent factor as the core, where the equivalent factor is the conversion coefficient between fuel thermal energy and electric energy. In the conventional ECMS strategy, the battery cannot continue to discharge when the state of charge (SOC) is lower than the target value. At this time, the motor mainly works in the battery charging mode, making it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 18 publications
0
25
0
Order By: Relevance
“…The control strategy based on optimization algorithm includes real-time optimization control strategy and global optimal control strategy. The core idea of real-time optimization control strategy is to minimize energy loss as much as possible during energy flow at any time, which is generally divided into equivalent consumption minimum strategy (ECMS) [18][19][20]and the control strategy based on model prediction [21][22][23]. However, the real-time optimization control strategy can only ensure that each step is optimal, but cannot ensure the global optimization, so it is difficult to apply in practice.…”
Section: A Litterature Reviewmentioning
confidence: 99%
“…The control strategy based on optimization algorithm includes real-time optimization control strategy and global optimal control strategy. The core idea of real-time optimization control strategy is to minimize energy loss as much as possible during energy flow at any time, which is generally divided into equivalent consumption minimum strategy (ECMS) [18][19][20]and the control strategy based on model prediction [21][22][23]. However, the real-time optimization control strategy can only ensure that each step is optimal, but cannot ensure the global optimization, so it is difficult to apply in practice.…”
Section: A Litterature Reviewmentioning
confidence: 99%
“…Therefore, the current research into this kind of EMS is focused on correcting the control parameters online according to the vehicle states, and the resulting EMSs are usually known as adaptive ECMS (A-ECMS). In [20], the ECMS was modified based on the following ideas: it is common that the SOC set for the power-maintaining hybrid vehicle ranges between 0.5 and 0.6, but there is still room for the continued use of electric energy; from statistical data, it is observed that the time that the vehicle spends at high acceleration is relatively short; hence, it will not cause the battery SOC to significantly decrease. Based on these premises, the ECMS was modified using an optimization algorithm to allow cautious use of the battery when its SOC is lower than the target.…”
Section: Ecms Emssmentioning
confidence: 99%
“…As a result, light load operation issues of the main ICE are transferred to the APU. Several optimal [8] and adaptive [9] energy management strategies were proposed and examined in the literature. System performance under these fairly complicated control structures is highly dependent on correct system representation and available information, which are not always available in real-time operating conditions.…”
Section: Introductionmentioning
confidence: 99%